INCIDENCE OF ANTERIOR UVEITIS IN AXIAL SPONDYLOARTHRITIS DURING SECUKINUMAB TREATMENT: TWO YEARS REAL LIFE EXPERIENCE FROM TURKBIO REGISTRY - Akleylek, C.; Akar, S.; Cinakli, H.; Sagir, R. Piskin; Coskun, B. N.; Karakas, A.; Yilmaz, N. (Elsevier, 2022)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 01-04, 2022 -- Copenhagen, DENMARK